La dignité humaine au théâtre des ombres - Mariève Lacroix (Cahiers Jean Moulin)
At a time when death drive is part of many contemporary legal debates, the questioning of mortal remains seems likely to be revisited. Oscillating between an object and a subject of law and struggling to find a third way which would allow to build a coherent status, the corpse runs up against the irreversibility of legal categories. If categorical difficulties of the law are a sign of its inability to describe the unspeakable, the corpse, yet, does not remain without legal protection. Through the prism of human dignity in contemporary Quebec law, the author apprehends the corpse’s legal protection.